Euclastes meridionalis (DE la FUENTE & CASADÍO) (Testudines: Pancheloniidae) from Danian levels of the Jagüel Formation at Cerro Azul, Northern Patagonia, Argentina - de la Fuente, Marcelo Saul (2009)
Complementary cranial and postcranial material of the Pancheloniidae Euclastes meridionalis (DE LA FUENTE & CASADÍO, 2000) from Danian levels of the Jagüel Formation (late Maastrichtian-Danian) at Cerro Azul locality (Rio Negro province, Argentina) is described. The new finding of E. meridionalis represents one of the few instances in which turtles with cranial remains similar to those previously referred to Osteopygis have well associated postcrania. This association allows recognition of the stem-Cheloniid condition of crania and postcrania of E. meridionalis (e.g. extremely extended secondary palate, shovel-like mandible, lateral process of the humerus close to the caput humeri, coracoid slightly shorter than the humerus, and a dorsal process of scapula forming relatively narrow angle with acromion).